Arginase II Promotes Intervertebral Disc Degeneration Through Exacerbating Senescence and Apoptosis Caused by Oxidative Stress and Inflammation via the NF-κB Pathway - Fudong Li (Frontiers Media S.A., 2021)
Intervertebral disc degeneration (IDD) has been generally accepted as the major cause of low back pain (LBP), which imposes massive clinical and socioeconomic burdens. Previous studies have demonstrated that oxidative stress and inflammation-induced senescence and apoptosis of nucleus pulposus cells (NPCs) are the main cellular processes that cause IDD. Arginase II (ARG2), an enzyme involved in a variety of pathological processes, including cellular senescence, apoptosis, oxidative stress, and inflammation, has been shown to promote degeneration in several degenerative diseases, including osteoarticular diseases. Based on previous studies, we hypothesized that ARG2 deficiency might be conducive to the treatment of IDD by inhibiting the dyshomeostasis of the extracellular matrix (ECM), and the oxidative stress and inflammatory response-induced senescence and apoptosis via NF-κB. In this study, we found that ARG2 deficiency inhibited senescence and apoptosis of NPCs, and degeneration of the ECM induced by oxidative stress and the inflammatory response. Similar results were found with the selective NF-κB pathway inhibitor JSH-23. In contrast, overexpression of ARG2 had the opposite effect. Taken together, our results suggest that ARG2 deficiency prevents IDD via NF-κB, and may therefore, be a potential therapeutic strategy for IDD.